Intake and digestibility of low-quality hay with nonprotein nitrogen supplementation in cattle - Mallmann, Giovanni Mateus; Patino, Harold Ospina; Silveira, André Luís Finkler da; Medeiros, Fábio Schuler; Knorr, Marcelo (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of nonprotein nitrogen supplementation levels on the digestibility of low-quality hay (Cynodon dactylon), which was offered ad libitum to Hereford bulls aging 17 months and weighing 220 kg. The evaluated treatments were: hay + no urea supplement; hay + supplement with 0.28 g urea kg-1 BW0.75; hay + supplement with 0.55 g urea kg-1 BW0.75; hay + supplement with 0.83 g urea kg-1 BW0.75 and hay + supplement with 1.11 g urea kg-1 BW0.75. Hay composition presented 3.86% of crude protein and 84.66% of neutral detergent fiber. Digestibility of organic matter, organic matter of forage, neutral detergent fiber, cellulose and hemicellulose were not affected by nonprotein nitrogen level; total intake of these components showed a quadratic response to nonprotein nitrogen supplementation. Organic matter metabolic fecal excretion was not affected by supplementation, suggesting a simultaneous increase in both passage (intake increase) and digestion rates (stable digestibility). The digestible organic matter intake showed a quadratic response with the increase of urea supplementation levels. The relationship between rumen degradable protein intake and digestible organic matter intake showed a maximization point, when rumen degradable protein intake was equivalent to 8.1% of digestible organic matter intake.
Keywords: protein supplementation; urea; starea; digestible organic matter; rumen degradable protein